SERS characterization of colorectal cancer cell surface markers upon anti‐EGFR treatment. Issue 3 (9th May 2022) - Lyu, Nana; Pedersen, Bernadette; Shklovskaya, Elena; Rizos, Helen; Molloy, Mark P.; Wang, Yuling
Abstract: Colorectal cancer (CRC) is the third most diagnosed and the second lethal cancer worldwide. Approximately 30–50% of CRC are driven by mutations in the KRAS oncogene, which is a strong negative predictor for response to anti‐epidermal growth factor receptor (anti‐EGFR) therapy. Examining the phenotype of KRAS mutant and wild‐type (WT) CRC cells in response to anti‐EGFR treatment may provide significant insights into drug response and resistance. Herein, surface‐enhanced Raman spectroscopy (SERS) assay was applied to phenotype four cell surface proteins (EpCAM, EGFR, HER2, HER3) in KRAS mutant (SW480) and WT (SW48) cells over a 24‐day time course of anti‐EGFR treatment with cetuximab. Cell phenotypes were obtained using Raman reporter‐coated and antibody‐conjugated gold nanoparticles (SERS nanotags), where a characteristic Raman spectrum was generated upon single laser excitation, reflecting the presence of the targeted surface marker proteins. Compared to the KRAS mutant cells, KRAS WT cells were more sensitive to anti‐EGFR treatment and displayed a significant decrease in HER2 and HER3 expression. The SERS results were validated with flow cytometry, confirming the SERS assay is promising as an alternative method for multiplexed characterization of cell surface biomarkers using a single laser excitation system. Abstract : Examining the phenotypes of KRAS mutant and wild‐type colorectal cancer cells during anti‐EGFR treatment may provide significant insights into drug resistance. Herein, we applied surface‐enhanced Raman spectroscopy (SERS) assay to detect four cell surface proteins on KRAS mutant and wild‐type cells over a 24‐day treatment, where SERS assay achieved multiplexed characterization of cell surface markers using a single laser excitation.